2018
DOI: 10.1038/s41467-017-02492-2
|View full text |Cite|
|
Sign up to set email alerts
|

Yolk sac macrophage progenitors traffic to the embryo during defined stages of development

Abstract: Tissue macrophages in many adult organs originate from yolk sac (YS) progenitors, which invade the developing embryo and persist by means of local self-renewal. However, the route and characteristics of YS macrophage trafficking during embryogenesis are incompletely understood. Here we show the early migration dynamics of YS-derived macrophage progenitors in vivo using fate mapping and intravital microscopy. From embryonic day 8.5 (E8.5) CX3CR1+ pre-macrophages are present in the mouse YS where they rapidly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
178
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(188 citation statements)
references
References 72 publications
8
178
1
1
Order By: Relevance
“…Therefore, differing maturational states of neural progenitor cells between males and females may signal for microglial colonization at different time points or to a different degree (VanRyzin et al, ). A recent report using intravital microscopy of CX3CR1 GFP/+ mice to trace pre‐macrophage trafficking from the fetal yolk sac to the embryo found that CX3CR1+ pre‐macrophages primarily entered the yolk sac vasculature and trafficked toward the embryo, and that the principal target of these yolk sac‐derived pre‐macrophages was the developing brain (Stremmel et al, ). However, the use of CX3CR1 to track pre‐macrophages may not be completely reflective of microglial colonization, as CX3CR1 is not expressed until ~E9.5, 2 days after yolk‐sac progenitors arise (Ginhoux et al, ; Hoeffel & Ginhoux, ).…”
Section: Sex Differences In Their Developmental Journey May Program Smentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, differing maturational states of neural progenitor cells between males and females may signal for microglial colonization at different time points or to a different degree (VanRyzin et al, ). A recent report using intravital microscopy of CX3CR1 GFP/+ mice to trace pre‐macrophage trafficking from the fetal yolk sac to the embryo found that CX3CR1+ pre‐macrophages primarily entered the yolk sac vasculature and trafficked toward the embryo, and that the principal target of these yolk sac‐derived pre‐macrophages was the developing brain (Stremmel et al, ). However, the use of CX3CR1 to track pre‐macrophages may not be completely reflective of microglial colonization, as CX3CR1 is not expressed until ~E9.5, 2 days after yolk‐sac progenitors arise (Ginhoux et al, ; Hoeffel & Ginhoux, ).…”
Section: Sex Differences In Their Developmental Journey May Program Smentioning
confidence: 99%
“…In support of the idea of distinct progenitor lineages, Tmem119 reporter animals showed expression in neonatal vasculature in addition to microglia, while Runx1 lineage progenitors did not contribute to early embryonic vasculature (Kaiser & Feng, ; Samokhvalov et al, ). While the molecular calling cards responsible for pre‐macrophage migration from the yolk sac to the brain are still unknown, the time‐frame of pre‐macrophage migration to the developing brain is similar to the early establishment of a vascular network in the brain (Stremmel et al, ). In NCX1 knockout mice lacking a heartbeat and functional blood circulation, microglia do not reach the brain (Ginhoux et al, ), suggesting that microglia migrate from the yolk sac to the fetal brain through the vasculature.…”
Section: Sex Differences In Their Developmental Journey May Program Smentioning
confidence: 99%
“…220 Macrophages are found in both blood and tissues, and despite their common origin in the bone marrow, tissue macrophages appear to exhibit an embryogenic development that is independent of that of blood macrophages or even of macrophages that migrate from the blood into tissues. [221][222][223] Macrophages perform a wide spectrum of functions in various tissues, including the removal of dead cells, as well as tissue remodeling and repair, which are associated with an elaborate response to foreign agents and infectious or noninfectious aggressors. [224][225][226] Given this, macrophages are crucial for the development of the organ-specific immune response, which acts on innate and adaptive immunity, frequently serving as a bridge between these two types of responses.…”
Section: Autophagymentioning
confidence: 99%
“…The heterozygous ( + / − ) CX3CR1eGFP embryos used in this study were obtained by crossing homozygous ( + / + ) CX3CR1eGFP mice (Jung et al, 2000) with C57BL/6 wild-type mice. CXCR1 is already expressed by immature macrophages and immature microglia at early developmental stages (from E9.5) in the mouse embryo (Rigato et al, 2011;Stremmel et al, 2018).…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%
“…d1) and CD68 (98.9 AE 1.3% n = 11 slices; 3 embryos)(Figure 3a2,a3,e), in addition to Iba1 at E12.5(Gordon, Pluddemann, & Martinez Estrada, 2014;Stremmel et al, 2018). 34.6 AE 4.9% of these embryonic macrophages only (n = 13 slices; 4 embryos) expressed CD11b(Figure 3b2,b3,e), which contrasts with microglia (≈ 90%)(Rigato et al, 2011).…”
mentioning
confidence: 96%